IMPLEMENTATION OF TEACHER CAREER DEVELOPMENT PROGRAM IN MAN 2 MODEL MEDAN - Wasiyem Wasiyem (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This study aims to describe the implementation of the teacher career development program at MAN 2 Model Medan. The focus of this study is the madrasah's efforts to facilitate teachers in aspects of career development in the form of promotions, teacher performance-based promotions, and transfers. This study uses a qualitative approach with a descriptive study method. Data were obtained using participant observation techniques, in-depth and specific interviews, and relevant document studies. Then, the data were analyzed through reduction techniques (data sorting), data presentation, and drawing conclusions. Furthermore, the data is declared valid (valid) after going through the triangulation technique test of sources and methods. The results of this study indicate that the implementation of the teacher career development program at MAN 2 Model Medan has been effective and efficient. This is marked by 3 (three) aspects of the career development program, first, promotion, with the stages of obtaining certificates as needed, continuous professional development (PKB) for teachers, conducting classroom action research (CAR), and submitting rank proposals. Second, performance-based promotion as measured by the level of diligent, disciplined, and teacher dedication to the institution. Third, transfer, which gives teachers the opportunity to continue their studies and transfer to other institutions (such as being a lecturer at UIN North Sumatra Medan, an employee of the North Sumatra Ministry of Religion Regional Office, or the Head of Madrasah).